2020
DOI: 10.1021/acs.est.0c06969
|View full text |Cite
|
Sign up to set email alerts
|

Hitchhiking Behavior in Bacteriophages Facilitates Phage Infection and Enhances Carrier Bacteria Colonization

Abstract: Interactions between bacteriophages (phages) and biofilms remain poorly understood despite the broad implications for microbial ecology, water quality, and microbiome engineering. Here, we demonstrate that lytic coliphage PHH01 can hitchhike on carrier bacteria Bacillus cereus to facilitate its infection of host bacteria, Escherichia coli, in biofilms. Specifically, PHH01 could adsorb onto the flagella of B. cereus, and thus phage motility was increased, resulting in 4.36-fold more effective infection of E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 60 publications
(128 reference statements)
2
40
0
Order By: Relevance
“…Flagellar mobility hence seems to be a driver for efficient phage transport by bacteria. Although a few studies have reported on preferential adsorption of phages to bacterial flagella [19], we found similar efficiencies of T4 adsorption to flagellated WT and non-flagellated △filM (Fig S1). T4 adsorption to the bacterial cell surface rather than to flagella was also confirmed by HIM imaging.…”
Section: Phage Co-transport With Hyphal-riding Bacteriasupporting
confidence: 65%
See 3 more Smart Citations
“…Flagellar mobility hence seems to be a driver for efficient phage transport by bacteria. Although a few studies have reported on preferential adsorption of phages to bacterial flagella [19], we found similar efficiencies of T4 adsorption to flagellated WT and non-flagellated △filM (Fig S1). T4 adsorption to the bacterial cell surface rather than to flagella was also confirmed by HIM imaging.…”
Section: Phage Co-transport With Hyphal-riding Bacteriasupporting
confidence: 65%
“…Although described for aquatic environments [19,41,42], little is known on viral co-transport with non-host microorganisms in vadose habitats; even though adsorption and subsurface cotransport of nano-colloids with organic or biological materials has been described nearly two decades ago [43]. Here, we show that Escherichia virus T4 can adsorb to the hyphal-riding soil bacterium P. putida KT2440 (Fig.…”
Section: Phage Co-transport With Hyphal-riding Bacteriamentioning
confidence: 66%
See 2 more Smart Citations
“…Examples include the transport of nonmotile bacteria 22 and spores 23 by swimming bacteria, gliding bacteria 24 , and zooplankton 25 . Electron microscopy images have shown that phage particles bind to bacterial flagella 26 and imaging of colonies infected by the phage suggests hitchhiking 26,27 . Do non-flagellated but motile bacteria transport phage particles and can one directly visualize phage transportation?…”
Section: Introductionmentioning
confidence: 99%